STUDENT BEHAVIOR REFLECTION ON ONLINE LEARNING IN WETON PERSPECTIVE - Astrid Wangsagirindra Pudjastawa (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
This study aims to find and analyze the meaning of online learning according to the reflection of student behavior based on Weton. With a qualitative approach, this study collected data from 5 students. The results showed that student A (Monday Wage) interpreted the practice of online learning as an effort to beautify traditional learning, while student B (Monday Pon) interpreted it as violating obligations between teachers and students, Student C (Tuesday Pahing) interpreted it as a mere technique, Student D (Thrusday Legi) considers it a challenge, and Siswa E (Wednesday Pon) considers online learning to be a burden for teachers. The behavior of student A does not reflect his character, while the behavior of students B to E reflects his character. The condition of the family environment, the school environment at the previous level, experience, and always positive thinking are factors that influence the formation of his character.